Pharmacist‐Led Antimicrobial Stewardship Optimizes Antibiotic Prescribing for Pediatric Community‐Acquired Pneumonia in Vietnam: A Quasi‐Experimental Before‐and‐After Study - Thang Nguyen; Trang Thuy Thi Tran; Thu Ngoc Chau Phan; Ly Truong Cam Nguyen; Phuong Minh Nguyen (JACCP: JOURNAL OF THE AMERICAN COLLEGE OF CLINICAL PHARMACY, 2026)
ABSTRACT Background Suboptimal antibiotic prescribing for pediatric community‐acquired pneumonia (CAP) contributes to avoidable harm and antimicrobial resistance, yet evidence on pharmacist‐led stewardship in low‐ and middle‐income countries remains limited. The objective of this study is to evaluate the impact of a pharmacist‐led antimicrobial stewardship intervention on antibiotic prescribing appropriateness for pediatric CAP in Vietnam. Methods We conducted a quasi‐experimental before‐and‐after study at a provincial maternal and pediatric referral hospital. Using monthly stratified systematic sampling, we reviewed 560 unique paper‐based medical records of children aged 2 months to 5 years who were hospitalized with a primary diagnosis of CAP and received systemic antibiotics (280 records in January–June 2024 and 280 in January–June 2025). The intervention comprised locally adapted prescribing guidance, two in‐person educational seminars, printed and digital prescribing tools, and case‐triggered face‐to‐face audit and feedback. Appropriateness was evaluated against the hospital protocol, Vietnamese national guidance, the Vietnam National Drug Formulary, and manufacturer information. Proportions were compared between periods; exploratory univariable logistic regression examined factors associated with inappropriate prescribing before the intervention. Results Overall appropriateness increased from 60.36% (169/280) to 86.79% (243/280; p < 0.001). Dose appropriateness increased from 67.14% to 90.71% ( p < 0.001), and dosing‐interval appropriateness increased from 90.36% to 98.57% ( p < 0.001). Before the intervention, age < 12 months (odds ratio [OR] 2.1, 95% confidence interval [CI] 1.3–3.5; p = 0.003) and combination therapy (OR 4.6, 95% CI 1.75–12.1; p = 0.001) were associated with inappropriate prescribing. Conclusion A structured pharmacist‐led stewardship intervention was associated with substantial improvement in antibiotic prescribing appropriateness for pediatric CAP, driven mainly by better dosing and dosing intervals. These findings support sustained pharmacist participation in pediatric antimicrobial stewardship in provincial Vietnamese hospitals.